RESEARCH ON MULTI-AXIAL FATIGUE LIFE OF CRANE WELD BASED ON STRUCTURAL STRESS METHOD - WANG Xin; YUE ZengKe; CAI FuHai; FU HeLing; XU ChengBin (Jixie qiangdu)
As an example of life evaluation of the weld between main girder and rigid leg of 580 t gantry crane based on structural stress method, the non-proportional stress characteristics of multi-axis are obtained by analyzing the working stress history of crane. The shell-solid mixed model with weld details in the dangerous position is built, and the multi-axial structural stress is obtained by combining the load spectrum with the ANSYS and Verity module of FE-SAFE software. The damage accumulation path is obtained by Path Dependent Maximum Range（PDMR）. Moment of Load Path（MLP） is introduced to realize the transformation from non-proportional loading path to proportional loading path. The fatigue life of the weld is estimated according to the master S-N curve and compared with the multi-axis proportional and uni-axial life estimation methods. It shows the necessity of multi-axial non-proportional fatigue analysis method, which provides reference for the complex multi-axial fatigue analysis of cranes.